Job Restructuring and Socio-Economic Security if Sri Lanka - Nawaratne, N.N.J. (My University, 2013)
After the economic liberalization in Sri Lanka, employment practices in the manufacturing industry and tertiary sector have changed gradually from traditional contractual arrangement and other terms and conditions of the work to nonstandard work arrangement or atypical employment practices. First part of this article distinguishes different types of atypical employment patterns and explains key features of the new type of employment relationship in Sri Lanka. Second part of the article, describes the major changes in the job security and its impact on socio-economic security in Sri Lanka by using the data from 600 Manufacturing Enterprises of the Enterprises Labor Flexibility & Security Survey (ELFS) for 2005-2006 conducted in manufacturing industry by the Social Policy Analysis and Research Center (SPARC) of the University of Colombo
Keywords: Job Restructuring and Socio-Economic Security if Sri Lanka